Pembelajaran Menulis Karangan Narasi Menggunakan Pemetaan Alur Pikir Siswa SMAN 9 Kota Kupang - Sanhedri Boimau; Jolis J.A Djami; Dixon E. M Take Bete (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This study refers to the low interest of students in writing narrative essays, students prefer to work on the questions in the Student Worksheet (LKS) compared to writing assignments, learning to write essays, especially teacher narrative essays only explain the material and assign students to write essays freely without guidance from the teacher, in writing narrative essays students struggle to arrange essays chronologically. In fact, writing learning itself has been applied in schools, especially in Class X2 students of SMA Negeri 9 Kupang City, but there are still many students who do not understand how to write essays, especially writing narrative essays. Based on that the solution applied is the researchers chose to use the Mind Mapping model which aims to explore information from both inside and outside the brain in order to obtain new ideas, new concepts according to students' understanding and prove the effectiveness of learning to write narrative essays. This research uses Pre Experimental in the form of Pretest-Posttest Design. The research data were obtained from observations, questionnaires, test results and field notes. The results showed that in the pretest, the average value of students was 51.73 or less categorized. The scores on the pretest have not yet reached the KKM that has been set. While the posttest increased by 29.63 or 57.27% to 81.36 and was in the good category. The expected benefit of this research is the development of educational theory theory, specifically the problem of the effectiveness of mind-mapping technique to develop students' writing potential, can improve and provide a more varied choice of learning techniques in the learning process and can create a fun learning activity, to improve skills student writing.